Virgin Coconut Oil Increases the Productivity of Broiler Chicken Post Avian Influenza Vaccination - Yuniwarti, EYW; Asmara, W; Artama, WT; Tabbu, CR (ANIMAL PRODUCTION, 2012)
Abstract. Chicken productivity is not only determined by body weight increase and feed efficiency but also disease resistance. Avian influenza (AI) is still an endemic in Indonesia. Highly mutative characteristic of AI causes unsuccessful vaccination to preventing chicken mortality; therefore, feed modulation alternatives are sought to raise body weight and body immune as well. Virgin coconut oil (VCO) contains fatty acid potential as antimicrobe and antivirus; VCO intake is therefore expected to increase chicken body immune. This research aimed at feed modulation to increase broiler chicken productivity. Forty broiler chicken of one day old (DOC) were used and the research applied Completely Randomized Factorial Design in which factor one was two vaccine levels namely AI-vaccinated chickens and AI-unvaccinated chickens. Factor two used four levels of VCO: 0, 5, 10, 15 mL/kg feed. DOC chickens were divided into eight treatment groups and repeated in five experiment units. Feed and water were given ad libitum. The result demonstrated that in spite of heterophile increase in AI-vaccinated VCO-given chickens, heterophile/lymphocyte ratio and feed intake were not significantly different among all treatment groups. With the highest body weight found in AI-vaccinated chickens given 10ml/kg feed VCO, it could therefore be concluded that VCO intake of 10mL/kg feed could raise body weight.Key words: heterophile, heterophile/lymphocyte ratio, feed intake, body weightAbstrak. Produktivitas ayam tidak hanya ditentukan oleh kenaikan bobot badan dan efisiensi pakan, tetapi juga ketahanan terhadap penyakit. Avian influenza (AI) masih merupakan wabah endemis di Indonesia. Sifat AI yang mudah bermutasi menyebabkan vaksinasi tidak selalu berhasil untuk mencegah kematian ayam, sehingga dicari alternatif modulasi pakan untuk meningkatkan bobot badan dan kekebalan tubuh. Virgin coconut oil (VCO) mengandung potensi asam lemak sebagai antimikroba dan antivirus, sehingga asupan VCO diharapkan dapat meningkatkan kekebalan tubuh ayam. Penelitian ini bertujuan untuk modulasi pakan untuk meningkatkan produktivitas ayam broiler. Empat puluh ayam broiler umur satu hari  (DOC) digunakan dalam penelitian yang menerapkan Rancangan Acak Lengkap Faktorial dengan faktor pertama dua level vaksinasi  yaitu ayam divaksin AI dan tidak divaksin AI. Faktor kedua adalah empat level VCO: 0, 5, 10, 15 mL  kg pakan. DOC ayam dibagi menjadi delapan kelompok perlakuan dan diulang dalam lima unit percobaan. Pakan dan air minum diberikan ad libitum. Hasilnya menunjukkan bahwa meskipun adanya kenaikan heterofil pada ayam yang divaksin AI dan diberi VCO, rasio heterofil/limfosit dan konsumsi pakan tidak berbeda secara signifikan pada semua kelompok perlakuan. Dengan bobot badan tertinggi ditemukan pada ayam yang divaksin AI dan diberi VCO 10 ml/kg pakan, maka dapat disimpulkan bahwa asupan VCO 10 mL/kg pakan dapat meningkatkan bobot badan. Kata kunci: heterophil, rasio heterophil/limfosit, konsumsi pakan, bobot badan EYW Yuniwartiet al/Animal Production 14(3):192-198, September 2012